2015
DOI: 10.1021/acs.joc.5b00697
|View full text |Cite
|
Sign up to set email alerts
|

Selective Secondary Face Modification of Cyclodextrins by Mechanosynthesis

Abstract: α-, β-, and γ-cyclodextrins (CDs) were modified on their secondary face by mechanosynthesis at room temperature using a laboratory-scale ball-mill. Mono-2-tosylated α-, β-, and γ-CDs were obtained in good yield from mixtures of native α-, β-, and γ-CDs, respectively, N-tosylimidazole, and an inorganic base, with each of them being in the solid state. The yields appeared to be dependent upon the nature of the base and the reaction time. A kinetic monitoring by (1)H NMR spectroscopy demonstrated that the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 81 publications
2
39
0
Order By: Relevance
“…The best result (96 % conversion) was obtained with 10 mol‐% citric acid at 30 Hz. Independent of the catalyst amount, these results corroborate previous studies regarding the crucial role of the ball‐mill frequency on the reaction yield 32,33. Actually, increasing the frequency of the milling resulted in an increase in the kinetic energy, which resulted in a transfer of more effective energy to the reactants.…”
Section: Resultssupporting
confidence: 90%
“…The best result (96 % conversion) was obtained with 10 mol‐% citric acid at 30 Hz. Independent of the catalyst amount, these results corroborate previous studies regarding the crucial role of the ball‐mill frequency on the reaction yield 32,33. Actually, increasing the frequency of the milling resulted in an increase in the kinetic energy, which resulted in a transfer of more effective energy to the reactants.…”
Section: Resultssupporting
confidence: 90%
“…While the mechanochemical manipulation of covalent bonds is hardly a brand new concept, its diffusion into carbohydrate chemistry, and particularly into CD derivatization, has been rather slow [2223]. The ability of HEBM to favour the nucleophilic substitution reaction of 6 I -monotosyl-β-CD has been demonstrated in a previous article [22].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently with works of Cravotto et al., we showed that regioselective mono‐2‐ O ‐tosylation of the secondary face of CDs proceeds quantitatively upon grinding on very short reaction times (ca. 1 min) via supramolecular means, the reactant (tosylimidazole) being included into the CD cavity . Similarly, highly selective processes were identified in the mechanically‐activated Au‐catalyzed reduction of nitroarenes in the presence of CDs .…”
Section: Figurementioning
confidence: 91%